(untitled) (Japan, 1979)
" NIPPON" has been enthusiastically receiced in many foreign countries, not to mention the foreign residents, businessmen, members of the diplomatic corps and tourist here. Its comprehensive and easy-to-read statistical surveys provode a true and clear picture of the basic situation confronting the people of present-day Japan,...
Keywords: Japan; History,Statistical